Gestión de talento humano en el comercial su economía de la ciudad Babahoyo periodo 2021. - Luna Lara, Mirian Valeria (2022)
The present case seeks to understand the problem that occurs in the establishment of the commercial Your Economy, which is why the Human Talent Management study was developed in the commercial YOUR ECONOMY in the city of Babahoyo period 2021, its owner Mr. Edgar Gaglay Tasghacho is the one who manages it, however, he does not have the necessary knowledge about the human resources area, being responsible for selecting, recruiting and correctly hiring the personnel that is part of the organization, since he does not have this area for the correct management of the functions and processes carried out by the staff that works in the company have been making decisions that then affect the business both economically and productively. This project aims to "Analyze the Management of Human Talent and its impact on the commercial Your Economy of the City of Babahoyo, due to the dissatisfaction of customers who do not receive the adequate attention they deserve, since the workers do not receive any type of benefits do not provide a quality service. As a research method, the inductive and deductive method was applied, since the application of these methods was fundamental for the investigation, since they start from the analysis of the specific and particular facts raised in the company. qualitative and quantitative, because the different types of concepts, theories were analyzed and the tabulations of the survey were made. of the data were the interview directed to the owner of the company and the survey to the workers of the company. It is evident that a high Percentage of the staff feels unmotivated and dissatisfied because they do not receive any kind of benefits.